2010
DOI: 10.14430/arctic971
|View full text |Cite
|
Sign up to set email alerts
|

A Step-Change in the Date of Sea-Ice Breakup in Western Hudson Bay

Abstract: over the last four decades there has been a trend to earlier summer breakup of the sea ice in western Hudson Bay, Canada. As this sea ice is critical for the polar bears that use it for hunting, the earlier breakup is believed to be a factor in the declining health of the regional polar bear population. Analysis of the change to earlier breakup using passive microwave satellite data is problematic because of currently unquantifiable systematic errors between different satellites. Analysis using Canadian sea-ic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 23 publications
1
13
0
Order By: Relevance
“…The dynamic, rather than climatic, aspect of seaice change is well exemplified in a recent satellite study by Scott and Marshall (2010), who aimed to resolve a dilemma: Whereas there has been a trend toward earlier summer breakup of sea ice in western Hudson Bay, Canada, which some authors (Stirling et al, 1999;Gagnon and Gough, 2005) have attributed to long-term warming in the region, Dyck et al (2007) report no regional warming trend has elapsed sufficient to have caused this change.…”
Section: Arctic Sea Icementioning
confidence: 99%
“…The dynamic, rather than climatic, aspect of seaice change is well exemplified in a recent satellite study by Scott and Marshall (2010), who aimed to resolve a dilemma: Whereas there has been a trend toward earlier summer breakup of sea ice in western Hudson Bay, Canada, which some authors (Stirling et al, 1999;Gagnon and Gough, 2005) have attributed to long-term warming in the region, Dyck et al (2007) report no regional warming trend has elapsed sufficient to have caused this change.…”
Section: Arctic Sea Icementioning
confidence: 99%
“…In the Arctic Ocean, potentially corrosive waters are found in the subsurface layer of the central basin (Jutterström and Anderson 2005 ;Anderson et al 2010 ), on the Chukchi/Beaufort Sea shelf Mathis et al 2012 ) and in outfl ow waters of the Arctic found on the Canadian Arctic Archipelago shelf (Azetsu- Scott et al 2010 ). On the Chukchi Sea, shelf waters corrosive to CaCO 3 occur seasonally in the bottom waters with unknown impacts to benthic organisms.…”
Section: The Western Arctic Oceanmentioning
confidence: 99%
“…The NFOR region also presents considerably different growing conditions because of frequent, cool northwesterly onshore winds from Hudson Bay (Rouse, 1991). Although Hudson Bay is typically completely ice-covered from January to May and ice-free from mid August to late October (Wang et al, 1994), the ice-free period has lengthened in recent years (Gagnon and Gough, 2005;Scott and Marshall, 2010).…”
Section: Study Areamentioning
confidence: 99%